Nakae Chomin’s World of Thought and Ideology of the Meiji Period through the “Gentleman” Character in “A Discourse by Three Drunkards on Government (Sansuijin Keirin Mondo)” - Yasemin Yazici (European Scientific Journal, ESJ, 2024)
From the second half of the 19th century, many intellectuals of the Meiji Japan serve as a referance for us in order to understand the roadmap of Japan which has revealed an important modernization story under the name of the Meiji Restoration. One of the enlightened thinkers we come across at this point is Nakae Chōmin. Nakae Chōmin, (1847-1901) contributed to the establishment of concepts such as freedom, equality, democracy and constitutionalism in the political memory of Japan through his articles. At the same time, he created a concept memory in the Japanese political thought and brought new concepts to the Japanese language.In this study, ideology analysis was made in “Sansuijin Keirin Mondō (A Discourse by Three Drunkards on Government)” which is called Nakae Chōmin’s masterpiece and conveys the ideas of the Meiji period to the reader through different characters. In this work, written with the Socratic dialogue method, the understanding of modernism, idealism, pacifism, freedom, equality, democracy etc. was examined by focusing on the “Gentleman”, one of the characters described as Nakae Chōmin’s alter ego. At the conclusion of the study, we have determined that a great majority of the ideas put forward by the character of “Gentleman” are also included in Nakae Chōmin’s intellectual framework, especially in the liberal views before 1891.